Effects of Exercise Therapy on Anxiety and Depression in Patients With Coronary Heart Disease: A Meta-Analysis of a Randomized Controlled Study - Wang, Lina; Sun, Yangli; Zhan, Jie; Wu, Zhiyuan; Zhang, Peiming; Wen, Xiaopeng; Ge, Shuqi; Han, Xu; Lu, Liming (Frontiers in Cardiovascular Medicine, 2021)
Abstract Objective: The purpose of this review was to evaluate the effect of exercise therapy on anxiety and depression symptoms in patients with coronary heart disease (CHD). Methods: A systematic review of papers published between January 2000 and February 2021 was conducted. MEDLINE, Embase, the Cochrane Library and Web of Science were searched. Meta-analysis was used to compare the results of the included studies. Bias risk assessment was performed using the Cochrane Collaboration bias risk tool. If half or more of the seven items in Randomized controlled trials (RCTs) were low-risk, then the RCT was considered low-risk research; otherwise, it was high-risk. Statistical analyses were performed using RevMan version 5.3 and STATA version 12.0. Results: We performed a meta-analysis of 11 randomized clinical studies including 771 subjects. Eight studies (73%) were of high quality. Compared with the control group, the exercise group showed a significant improvement in anxiety (standard mean difference (SMD)=-0.61; 95% confidence interval (CI):-0.86, -0.35). The depression level in the exercise group was also significantly reduced (SMD=-0.48; 95% CI:-0.92, -0.04). Aerobic fitness and athletic endurance also improved (mean difference (MD) =0.77; 95% CI: 0.58, 0.95; and MD=20.69; 95% CI: 6.91, 34.46; respectively). Conclusions: This meta-analysis suggests that exercise therapy may be effective in alleviating anxiety and depression symptoms in patients with coronary heart disease. Due to methodological weaknesses, rigorous research needs to be designed to further confirm the effectiveness of exercise therapy in improving the mental health of patients with coronary heart disease.